Cell-free DNA maps COVID-19 tissue injury and risk of death and can cause tissue injury - Andargie, Temesgen E.; Tsuji, Naoko; Seifuddin, Fayaz; Jang, Moon Kyoo; Yuen, Peter S.T.; Kong, Hyesik; Tunc, Ilker; Singh, Komudi; Charya, Ananth; Wilkins, Kenneth; Nathan, Steven; Cox, Andrea; et al. (JCI insight, 2021)
INTRODUCTIONThe clinical course of coronavirus 2019 (COVID-19) is heterogeneous, ranging from mild to severe multiorgan failure and death. In this study, we analyzed cell-free DNA (cfDNA) as a biomarker of injury to define the sources of tissue injury that contribute to such different trajectories.METHODSWe conducted a multicenter prospective cohort study to enroll patients with COVID-19 and collect plasma samples. Plasma cfDNA was subject to bisulfite sequencing. A library of tissue-specific DNA methylation signatures was used to analyze sequence reads to quantitate cfDNA from different tissue types. We then determined the correlation of tissue-specific cfDNA measures to COVID-19 outcomes. Similar analyses were performed for healthy controls and a comparator group of patients with respiratory syncytial virus and influenza.RESULTSWe found markedly elevated levels and divergent tissue sources of cfDNA in COVID-19 patients compared with patients who had influenza and/or respiratory syncytial virus and with healthy controls. The major sources of cfDNA in COVID-19 were hematopoietic cells, vascular endothelium, hepatocytes, adipocytes, kidney, heart, and lung. cfDNA levels positively correlated with COVID-19 disease severity, C-reactive protein, and D-dimer. cfDNA profile at admission identified patients who subsequently required intensive care or died during hospitalization. Furthermore, the increased cfDNA in COVID-19 patients generated excessive mitochondrial ROS (mtROS) in renal tubular cells in a concentration-dependent manner. This mtROS production was inhibited by a TLR9-specific antagonist.CONCLUSIONcfDNA maps tissue injury that predicts COVID-19 outcomes and may mechanistically propagate COVID-19-induced tissue injury.FUNDINGIntramural Targeted Anti-COVID-19 grant, NIH.